UJI AKTIVITAS ANTIDIABETES EKSTRAK ETANOL BIJI ALPUKAT (Persea americana Mill.) SECARA IN VITRO DENGAN MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Zulhijja .S, Faradiba; Abidin, Zainal; Wati, Aulia (PHARMACY UMI JOURNAL SYSTEM, 2023)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia, which is caused by insulin resistance and dysfunction of insulin secretion. Avocado is used as a traditional medicine to treat various diseases, one of which is the seed of the avocado which contains alkaloids, polyphenols, tannins, flavonoids, triterpenoids, quinones, saponins, monoterpenes and sesquiterpenes and can lower blood glucose levels. The aim of this study was to determine the antidiabetic potential of ethanol extract of avocado seeds (Persea americana Mill.) in vitro using the Nelson Somogyi method. The test began with preparing a series of sample ethanol extract concentrations with concentrations of 40, 50 and 60 ppm using a UV-Vis spectrophotometer measured at a wavelength of 745 nm. The results of testing the anti-diabetic activity by the test samples were able to show the effectiveness of reducing glucose levels in vitro by showing the EC50 value in the ethanol extract sample was 59.1018 μg/mL. From the results of the study it can be concluded that the ethanol extract of avocado seeds (Persea americana Mill) has activity in reducing glucose levels.